Zenarchopterus takaoensis (Perciformes: Zenarchoperidae), a new estuary garfish from southwestern Taiwan - Liao, Yun-Chih; Thiel, Ralf; Chang, Chih-Wei (Zootaxa, 2024)
Species of the genus Zenarchopterus are marine, brackish, and freshwater fishes that have modified dorsal-fin and anal-fin rays in adult males. There are 19 valid species worldwide. Three species have been recorded from Taiwan, namely Zenarchopterus buffonis (Valenciennes, in Cuvier & Valenciennes, 1847), Z. dispar (Valenciennes, in Cuvier & Valenciennes, 1847), and Z. dunckeri Mohr, 1926. However, Collette and Su (1986) noted one uncertain species (female, labeled “Zenarchopterus sp., Takao, Formosa, Hans Sauter, V–VII 1907”) in the Museum of Nature Hamburg (ZMH) from southern Taiwan. This species has only nine pectoral-fin and anal-fin rays, a longer snout, and does not agree well with any other species. In this study, Zenarchopterus takaoensis sp. nov. is described based on seven newly collected specimens from southwestern Taiwan and one (ZMH 6543, 59.4 mm SL) from southern Taiwan. This new species differs from its congeners by the following combination of characters: snout slightly longer, prominent pigmentation or dark mark on snout; nine anal-fin rays, 6th anal-fin ray not elongated or thickened in adult male; dorsal body pigmented with three longitudinal dashed lines, oval-like dashed pigmentation on dorsal lateral series scales; anterior lateral stripe on body in dashed line, ventral body with one longitudinal dashed line. In this study, specimens were examined and compared; morphological evidence revealed it is a hidden species. Taxonomic accounts, distribution, and a key to the congener species of Taiwan, along with color photographs of the new species, are provided.